2021
DOI: 10.1080/02699052.2021.1942551
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sports-related concussion in elite para athletes – a 52-week prospective study

Abstract: Objective: To assess the 52-week incidence proportion and incidence rate of sports-related concussion (SRC) among elite Para athletes, and to analyze the injury mechanisms. Method: In total, 70 male and 37 female Swedish elite Para athletes (median age 29 years) with vision, physical and intellectual impairment, weekly self-reported sports-related injuries including concussion in an eHealth application adapted to Para athletes. Descriptive statistics were used to assess the incidence rate and incidence proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…16,17 Comparing a group of Swedish winter parasport athletes (including para-alpine skiing, cross country skiing, ice hockey and wheelchair curling, n = 19), a concussion IR of 0.4 concussion/1000 athlete-hours was found, which is remarkably lower than that found in our survey. 18 Our findings support the findings of Hawkeswood et al 1 that concussion is a major concern in sledge hockey based on a 10-point ranking scale of participant's perceived frequency of the injury occurring. In our survey, head/face injuries (17/47, 36.1%) were the most common injury location followed by upper extremity (12/47, 25.5%).…”
Section: Discussionsupporting
confidence: 90%
“…16,17 Comparing a group of Swedish winter parasport athletes (including para-alpine skiing, cross country skiing, ice hockey and wheelchair curling, n = 19), a concussion IR of 0.4 concussion/1000 athlete-hours was found, which is remarkably lower than that found in our survey. 18 Our findings support the findings of Hawkeswood et al 1 that concussion is a major concern in sledge hockey based on a 10-point ranking scale of participant's perceived frequency of the injury occurring. In our survey, head/face injuries (17/47, 36.1%) were the most common injury location followed by upper extremity (12/47, 25.5%).…”
Section: Discussionsupporting
confidence: 90%
“…6 Lexell et al demonstrated that Swedish Para athletes with vision impairment reported a significantly higher incidence of sport-related concussion, with collisions being the most common injury mechanism. 7 In different contexts, these studies demonstrate that collisions involving head and neck impacts occur commonly to blind footballers and visually impaired Swedish Para athletes report higher rates of concussions than their Para athlete counterparts with normal vision, but the risk of concussion in para sports is not known.…”
Section: Original Researchmentioning
confidence: 89%
“…Fitzpatrick et al measured kinematic forces, using head-mounted impact sensors, on seven members of a blind football team over 6 months and demonstrated 3.29 mean low magnitude impacts per player per 50 min match, confirming regular match head impacts and therefore concussion risk 6. Lexell et al demonstrated that Swedish Para athletes with vision impairment reported a significantly higher incidence of sport-related concussion, with collisions being the most common injury mechanism 7. In different contexts, these studies demonstrate that collisions involving head and neck impacts occur commonly to blind footballers and visually impaired Swedish Para athletes report higher rates of concussions than their Para athlete counterparts with normal vision, but the risk of concussion in para sports is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding and guidelines for assessment, management and prevention of concussion in para-athletes are lacking. 7 Athletes with visual impairments have been shown to be at higher risk of concussion, 8 whereas an epidemiological study of the Tokyo Paralympics showed zero concussion occurrences in blind football competitions. 9 This gap may be explained for two reasons.…”
Section: Introductionmentioning
confidence: 99%